GE_GERICHTE P/272/2012 vom 27. März 2019 - GE Cour de justice (2019)
DÉFENSE D'OFFICE ; INDEMNITÉ(EN GÉNÉRAL) ; INTÉRÊT MORATOIRE ; TARIF(EN GÉNÉRAL) ; AVOCAT ; STAGE | CP.123; CP.128; LCR.902; LCR.92; LCR.96; LCR.901; LCR.95; LCR.99; LCR.93; LCR.961; LCR.952; CPP.135; RAJ.16; RAJ.17; RAJ.23